Approach to the basic needs in patients on invasive ventilation using eye‐tracking devices for non‐verbal communication. Issue 3 (18th October 2021) - Ull, Christopher; Hamsen, Uwe; Weckwerth, Christina; Schildhauer, Thomas Armin; Gaschler, Robert; Waydhas, Christian; Jansen, Oliver
Abstract: Purpose: To analyze the feasibility of eye‐tracking (ET) devices as a communicative approach to the basic needs (BN) of intensive care unit (ICU) and invasively ventilated nonverbal patients. Methods: Prospective, monocentric, and observational study including all patients without delirium, with an endotracheal tube or tracheostomy tube, with a history of invasive ventilation for more than 48 h, and inadequate nonverbal communication skills. The investigation was performed with commercially available ET devices (Tobii Dynavox I‐15+) to express BN of ICU patients following a standardized 30‐item yes‐or‐no questionnaire. Results: A total of 64 patients with a mean age of 58.6 years were included. The main diagnoses for ICU admission were major trauma (43.6%), sepsis (21.8%), and acute abdomen (15.6%). Pain during repositioning (69%), thirst (69%), sleep disorders (66%), fatigue (64%), and anxiety regarding the lifelong need for assistance (64%) were the main problems reported by the patients. However, most of the patients described expectations of health improvement (78%), good family support (66%), and an improvement in quality of life due to the use of ET devices (67%). Conclusion: The use of ET in selected ICU patients with impaired communication is feasible, allowing them to express their BN. Apart from knowing the patients' individual BN, the results of our BN questionnaire may provide guidance for improvement measures in the care of patients in the ICU who are unable to speak. We believe that ET is useful for inquiring about and expressing BN and, therefore, may be capable of improving patient‐medical team interactions and patient satisfaction. Abstract : The use of eye‐tracking (ET) in 64 selected critically ill patients with impaired communication was feasible for determining their basic needs (BN). Apart from knowing the patients' individual BN, the results of our BN questionnaire may provide guidance for improving care for patients in the ICU who are unable to speak. We believe ET is useful for inquiring about and expressing BN and therefore may be capable of improving patient medical team interactions and patient satisfaction.